2015
DOI: 10.1111/jch.12591
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Cardiac Markers and Biomarkers With Blood Pressure of Middle‐Aged Marathon Runners

Abstract: Runners with exercise-induced high blood pressure have recently been reported to exhibit higher levels of cardiac markers, vasoconstrictors, and inflammation. The authors attempted to identify correlations between exercise-related personal characteristics and the levels of biochemical/cardiac markers in marathon runners in this study. Forty healthy runners were enrolled. Blood samples were taken both before and after finishing a full marathon. The change in each cardiac/biochemical marker over the course of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 34 publications
1
22
0
1
Order By: Relevance
“…Systolic blood pressure has not been included in the multiple regression analyses in previous studies (10,12,13). However, some smaller studies have reported bivariate correlations between blood pressure and exercise-induced cTn increase (21,22). Our finding is intriguing, and in line with the recent mechanistic study by Weil and al., that observed a transient increase in cTnI following phenylepinephrine infusion in a pig model (7).…”
Section: Systolic Blood Pressuresupporting
confidence: 80%
“…Systolic blood pressure has not been included in the multiple regression analyses in previous studies (10,12,13). However, some smaller studies have reported bivariate correlations between blood pressure and exercise-induced cTn increase (21,22). Our finding is intriguing, and in line with the recent mechanistic study by Weil and al., that observed a transient increase in cTnI following phenylepinephrine infusion in a pig model (7).…”
Section: Systolic Blood Pressuresupporting
confidence: 80%
“…Sample size was estimated based on power test analysis through the level of the effects (changes wanted to be observed) taken from previous studies [25,26] for three main outcome variables (NT-proBNP, hs-TnI and Gal-3). Detailed data for sample size estima tion is given in ▶ table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Another important confounding factor is the different experience of runners. Thus, 26 studies (4 studies with male and female participants, and 15 studies with only male participants) reported a range of 4–17.5 years of experience with competitions (e.g., marathon, and ultra-marathon experience) (Schobersberger et al, 2000 ; Fallon et al, 2001 ; Nieman et al, 2003 , 2016 ; Suzuki et al, 2003 ; Tomaszewski et al, 2003 ; Kim et al, 2007 , 2015 ; Millet et al, 2011 ; Jee and Jin, 2012 ; Vaisberg et al, 2012 , 2013 ; Waśkiewicz et al, 2012 ; Bernecker et al, 2013 ; Jee et al, 2013 ; Karstoft et al, 2013 ; Kasprowicz et al, 2013 ; Kłapcinska et al, 2013 ; Saugy et al, 2013 ; Shin and Lee, 2013 ; Wilhelm et al, 2014 ; Grabs et al, 2015 ; Hewing et al, 2015 ; Mrakic-Sposta et al, 2015 ; Krzeminski et al, 2016 ; Mohamed et al, 2016 ). However, 25 studies did not report this information (Fehrenbach et al, 2000 ; Mattusch et al, 2000 ; Neidhart et al, 2000 ; Niess et al, 2000 ; Suzuki et al, 2000 ; Bonsignore et al, 2002 ; Uchakin et al, 2003 ; Peters et al, 2004 ; Siegel et al, 2007 ; Ng et al, 2008 ; Papassotiriou et al, 2008 ; Chimenti et al, 2009 , 2010 ; Auersperger et al, 2012 ; Nickel et al, 2012 ; Rehm et al, 2013 ; Santos et al, 2013 ; Bachi et al, 2015 ; Gill et al, 2015b ; Arakawa et al, 2016 ; Nielsen et al, 2016 ; Stuempfle et al, 2016 ; Vernillo et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%